Antitumor Activity of Cyclodextrin-based Supramolecular Platinum Prodrug In vitro and In vivo - Zhang, Yu-Hui; Wang, Jie; Xin, Siqintana; Wang, Li-Juan; Sheng, Xianliang (Letters in Drug Design & Discovery, 2019)
Background: Considering the limitations of cisplatin in clinical application, there is ongoing research to fabricate new platinum-containing prodrug which are highly effective to tumor cells and have low toxicity to normal cells. Methods: In this study, a cyclodextrin-based supramolecular platinum prodrug that is 6,6’-ophenylenediseleno- bridged bis (β-cyclodextrin)s (CD) and its potassium tetrachloroplatinate(II) complex was reported. The cytotoxicity experiments were performed to evaluate the anticancer activities of supramolecular prodrug in vitro by means of MTT assay. The practical application of supramolecular prodrug in tumor treatment in vivo were evaluated using BALB/c nude mice model bearing Hela cancer cells. Results: Compared with commercial anticancer drug cisplatin, the resultant cyclodextrin-based platinum prodrug exhibited comparative anticancer effect but with much lower toxicity side effects in vitro and in vivo. Conclusion: The cyclodextrin-based supramolecular platinum prodrug displayed antitumor activity comparable to the commercial antitumor drug cisplatin but with lower side effects both in vitro and in vivo, implying that the two adjacent cyclodextrin cavities not merely act as desired solubilizer, but also endowed the prodrug with cell permeability through the interaction of cyclodextrin with phospholipids and cholesterol on cell membrane.
Keywords: cisplatin